10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
People with intellectual disabilities (ID) are 5-10 times more likely to have hearing loss than the general population, yet it often remains undetected and untreated. To address this gap, the study HörGeist examined the feasibility, outcomes, barriers, and costs of an outreach program with hearing screening, diagnostics, intervention, and monitoring in everyday environments to implement a universal program in Germany. This report outlines ear and hearing care status before and after inclusion in the program and compares outcomes with standard care and a clinic-based invitation model. In a population-based, age-stratified cohort study, 1053 participants with ID (37% female; age 1-90 years) received screening and reference measurements in nurseries, schools, workplaces, and residences. When screening indicated possible hearing loss, on-site diagnostics and therapy were provided or referrals issued. A comparison cohort of 141 individuals with ID was invited to a clinic for identical procedures; none participated. All procedures were repeated after 1 year. Hearing loss was known in 14% of outreach participants at study entry; 8.7% had previously received hearing aids, but fewer than half (4.3%) used them. The program diagnosed hearing loss in 44% of participants, with 70% previously undiagnosed. After screening, 27% received therapy recommendations, but only 37% adhered to them (30% for hearing-aid prescriptions). Undertreated hearing loss declined only slightly, from 43% to 38%, over time. Major barriers included refusal by caregivers (31%) and participants (33%), often appearing to be linked to limited awareness of the treatability and consequences of hearing loss, as well as time and staff shortages. Outreach hearing screening programs are highly necessary, feasible, and effective in detecting hearing loss in people with ID, but substantial care gaps persist. Implementation requires public and professional awareness and rehabilitation strategies that include hearing and communication training and actively involve individuals with ID and their caregivers.